1995
DOI: 10.1017/s0317167100039482
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Exposure to Manganese in Rural Well Water Has No Neurological Effects

Abstract: ABSTRACT:Background: There is debate on the neurological impact of chronic exposure to Manganese (MN). Methods: MN burden from rural well water was studied cross-sectionally in two proband cohorts from rural dwellings located in northern Germany. Both cohorts had exposure times for up to 40 years and were separated on the basis of well water MN content. Group A (41 subjects; mean age 57.5 years) was exposed to MN water contents of at least 0.300 mg/1 (range 0.300 to 2.160), while group B (74 subjects; mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 19 publications
0
32
1
1
Order By: Relevance
“…It should be noted that the highest Mn levels in drinking water in this study are a factor of 10 lower than the levels shown to cause severe manganese poisoning in the early Japanese study. On the other hand, a study in Germany did not demonstrate increased neurological impairment associated with Mn in drinking water (Vieregge et al, 1995). In this latter study, Mn drinking water levels for the most exposed group were lower than those for the most exposed group in the Greek study and the study population was younger.…”
Section: Environmental Studiescontrasting
confidence: 63%
“…It should be noted that the highest Mn levels in drinking water in this study are a factor of 10 lower than the levels shown to cause severe manganese poisoning in the early Japanese study. On the other hand, a study in Germany did not demonstrate increased neurological impairment associated with Mn in drinking water (Vieregge et al, 1995). In this latter study, Mn drinking water levels for the most exposed group were lower than those for the most exposed group in the Greek study and the study population was younger.…”
Section: Environmental Studiescontrasting
confidence: 63%
“…Several studies have suggested that exposures to aluminum, copper, and lead are risk factors for PD, 10,73,74 but no such link has been found for manganese. 10,12,[74][75][76][77][78][79][80] In one study conducted in southern Quebec (Canada), involving 42 parkinsonian patients compared with a group of 84 matched controls, a slightly increased risk for PD was found to be associated with occupational exposure to manganese, iron, and aluminum, but this association did not reach statistical significance. 81 In a study of WWII Twins Cohort, involving 163 twin pairs, in which a blinded industrial hygienist estimated lifetime occupational manganese exposure intensity and duration, twins with PD were less likely to have ever been exposed to manganese than their control twin (OR ϭ 0.36) and had a shorter average duration of manganese exposure than did controls.…”
Section: How Is the Diagnosis Of Manganese-induced Parkinsonism Confimentioning
confidence: 99%
“…The reduced compensatory capacity of older persons’ nervous systems has been proposed as an explanatory mechanism for their apparent vulnerability (Kondakis et al 1989). However, Vieregge et al (1995) did not observe differences when comparing neurologic status and neurotoxic symptoms in adults > 50 years of age drinking water containing Mn concentrations 300–2,160 μg/L to those drinking water containing Mn < 50 μg/L. Small sample size, wide variation of Mn concentrations, and the use of extensive exclusion criteria that could have excluded persons presenting neurotoxic effects of Mn exposure (i.e., history of treatment for psychiatric disorder, neuroorthopedic incapacity for movement of hand and fingers) might have limited the validity of this study.…”
mentioning
confidence: 99%